IMPLEMENTASI KUGI PADA BATAS NAGARI DI KECAMATAN BASA AMPEK BALAI TAPAN MENGGUNAKAN APLIKASI CARTOVIEW - Sepiati, Dian; Yulfa, Arie (JURNAL BUANA, 2024)
KUGI (Katalog Unsur Geografi Indonesia) is the assignment of codes and code structures, determination of types, operations, attributes, associations and documentation rules for elements presented in geographic elements. The increasing need for geospatial data (DG) and Geospatial Information (IG) makes KUGI standardization of geospatial information indispensable to facilitate data processing. The purpose of KUGI is to make the data uniform. The initial stage in the KUGI standardization process at the nagari boundaries in the Basa Ampek Balai Tapan sub-district is the process of collecting data and adjusting attributes according to the template from the KUGI website. Next, fill in the attributes according to the rules that have been provided. The results of this Geospatial information can be stored and uploaded to various geoportal platforms. One of them is the Cartoview application.